Exploring the Use of Game-based Ice-breaking Activities by English Teachers during the Teaching and Learning Process - Sari, Karina Cahya; Rusfandi, Rusfandi; Herawati, Siane (Journal of English Language and Education, 2024)
Game-based ice-breaking activities are essential for increasing student engagement and motivation during English lessons. Previous studies have highlighted their effectiveness in creating a learning environment that focuses on student experiences. This study aims to fill the gap by exploring the types of game-based icebreaker activities used by English teachers and their impact on them. A qualitative descriptive method was employed, collecting data from three elementary school teachers in Malang, East Java, through observation and interviews. The study found that both non-digital and digital games were used as ice-breaking activities to foster a more interactive learning environment. These activities strengthened teacher-student relationships and encouraged creativity in teaching methods. However, challenges such as time constraints, limited resources, and managing student behavior were observed. These findings indicate the importance of integrating games into teaching strategies to enhance the relationships between teachers and students, thereby improving the classroom atmosphere and promoting creativity in teaching methods. They also highlight the need for teacher training programs to address challenges such as time constraints, limited resources, and managing student behavior when implementing games.